Analysis Of the Validity of the Circular Quest: Detective Orbit Board Game as a Learning Medium for the Topic - Magdalena Wona Wea; Maria Ursula Jawa Mukin; Claudya Mariska M. Maing (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2026)
Teaching physics on the topic of Uniform Circular Motion requires instructional media capable of facilitating the visualization of concepts while enhancing student engagement in the learning process. Before being used in instruction, the media must undergo a validation process to ensure its suitability in terms of content, pedagogy, media, and visual design. This study aims to analyze the feasibility of the “Circular Quest: Detective Orbit” board game for the topic of Uniform Circular Motion based on validation results from six validators—comprising three subject matter experts and three media experts. This study is part of a research and development (R&D) project using the ADDIE model, limited to the Development phase. The Analysis and Design phases were conducted as the foundation for media development, while this article focuses on the analysis of the experts’ validation results regarding the media’s suitability. Data were collected using a media validation sheet and analyzed quantitatively using Aiken’s V validity coefficient, with a criterion of V ? 0.89 indicating validity, while V < 0.89 indicates invalidity. The research results show that the aspect of content completeness received a score of 0.93; curriculum alignment and pedagogical suitability, 0.92; content suitability, 0.94; media suitability and functionality, 0.97; while the aspect of visual design received a score of 0.80, thus failing to meet the validity criteria. Overall, the media validation results yielded an Aiken’s V validity coefficient of 0.91, falling into the “valid” category. These results indicate that the “Circular Quest: Detective Orbit” board game has met the validity criteria based on expert assessments. Although the visual design aspect has been revised according to the validators’ feedback, the revised version has not yet undergone a revalidation process. Therefore, further research is recommended to conduct additional validation, practicality testing, and effectiveness testing through implementation with students.